Developers' perspectives on the root causes of project postponement in Malaysia / Nur Syahirah Ahmad Shabri and Shahela Mamter - Ahmad Shabri, Nur Syahirah; Mamter, Shahela (2020)
The construction sector in Malaysia is one of the key sectors contributing to Malaysia's economic development. In the construction industry, a lot of issues arise before the completion of the project, some of the projects will be postponed, delayed or abandoned. Although past studies have examined the postpone, abandoned, delay and the phenomenon of projects postponement still occurring in Malaysia. Therefore, the aim of this dissertation is to investigate undiscovered causes of the phenomenon of project postponement in Malaysia. Three objectives have been formulated, namely, to identify the root causes of the postpone project occurs in Malaysia, to determine the impact of the root causes to the project completion period, and to recommend solutions to mitigate the postponement of projects in Malaysia. In order to achieve the aim of this study, questionnaires have been distributed to developers in Perak. The collected data were analyzed in descriptive analysis by using Statistical Package for the Social Science (SPSS). There are four factors that contributed to the root causes of project postponement identified, namely client, contractor, consultant, and external factor. The findings identified sixteen solutions to mitigate the postponement of project in Malaysia. This study reveals three new findings which are accurate cost and initial time estimates, preparing SOP for unpredictable external factors and the most period project postpones less than one year and more than one year caused by the contractor. In conclusion, contractors gives the highest impact that contribute to project postponement.